2021
DOI: 10.1002/app.51010
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(butylene succinate) vitrimer with thermal shape stability via transesterification reaction

Abstract: Poly(butylene succinate) (PBS) refers to a high‐performance biodegradable polymer employed to substitute petroleum polymers that cause environmental issues. However, PBS exhibits the defect of flowing above the melting point and rapid dripping for its poor melt strength. Accordingly, this study proposed a novel method to fabricate PBS vitrimer by exploiting reactive extrusion technology to mix diepoxide with PBS and then by employing zinc acetate as a catalyst to crosslink the PBS. Therefore, after the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Much of the work to date on vitrimers has focused on their dynamic properties (such as stress relaxation times or viscosities) as well as the mechanical properties before and after recycling. Most vitrimers are studied in the amorphous state, but recent investigations have probed how dynamic bonds impact the nanostructure, including phase separation and crystallization. , If vitrimers are slated to be replacements for commodity plastics, an improved understanding of assembly, crystallization, and phase separation is needed for the broad range of polymer applications. One of the earliest examples of this was in polyethylene vitrimers, which have been shown to form nanoscale clusters of the dioxaborolane cross-linking moieties within the incompatible matrix, which provides additional cross-linking and impacts the stress relaxation of the network (Figure a). , Understanding when the dynamic bonds will phase separate from the matrix is critical for the interpretation of stress relaxation and self-healing investigations.…”
Section: Self-assembly In Vitrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the work to date on vitrimers has focused on their dynamic properties (such as stress relaxation times or viscosities) as well as the mechanical properties before and after recycling. Most vitrimers are studied in the amorphous state, but recent investigations have probed how dynamic bonds impact the nanostructure, including phase separation and crystallization. , If vitrimers are slated to be replacements for commodity plastics, an improved understanding of assembly, crystallization, and phase separation is needed for the broad range of polymer applications. One of the earliest examples of this was in polyethylene vitrimers, which have been shown to form nanoscale clusters of the dioxaborolane cross-linking moieties within the incompatible matrix, which provides additional cross-linking and impacts the stress relaxation of the network (Figure a). , Understanding when the dynamic bonds will phase separate from the matrix is critical for the interpretation of stress relaxation and self-healing investigations.…”
Section: Self-assembly In Vitrimersmentioning
confidence: 99%
“…While the crystallization of polymers has been heavily investigated for decades, melting temperatures ( T m ) have only been reported in a limited number of vitrimers based on PE, , PDMS, poly­(butylene terephthalate), and poly­(butylene succinate) . It has recently been reported that the presence of dynamic bonds in vitrimers allows for crystallization, which is not possible in a permanent network with the same linker (Figure b) .…”
Section: Self-assembly In Vitrimersmentioning
confidence: 99%
“…For instance, Athanassiou et al have reported biodegradable epoxidized soybean oil acrylate vitrimers. 10 Degradable vitrimers prepared from poly(butylene succinate), 11 vanillin, 12 polycarbonate, 13 and glycyrrhizic acid 14 have also been reported, and the recent review of Shaver highlights the most recent achievements in this field. 15 However, the development of vitrimers with both a high glass-transition temperature (T g ) and degradability under mild conditions is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent efforts have been devoted to design and fabricate polyester vitrimers, which has been demonstrated as an efficient way to improve their melt strength, processing property, and recyclability through constructing dynamic cross-links. , However, it is noticed that there are some severe problems that limited the large-scale production and practical application of currently reported polyester vitrimers. Demongeot et al, Zhou et al, and Farge et al .…”
Section: Introductionmentioning
confidence: 99%